2019
DOI: 10.1186/s40851-019-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Same but different: aquatic prey capture in paedomorphic and metamorphic Alpine newts

Abstract: Paedomorphosis describes the retention of larval characters in adult stages and is widespread amongst salamanders. Salamandrid newts exhibit facultative paedomorphosis, where paedomorphic and metamorphic adult forms coexist in the same population. Previous studies have shown that prey capture kinematics do not differ between paedomorphic and metamorphosed ambystomatid salamanders, despite diverging morphology and prey capture performance. It remained unclear, however, whether the stereotypy of prey capture kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 66 publications
(95 reference statements)
0
17
0
Order By: Relevance
“…It was recently shown that metamorphosed salamandrid newts use loop-like movements of their hyobranchial apparatus (i.e., tongue) to translate food across the palatal dentition (i.e., tongue-palate rasping) [21]. It has also been suggested that salamandrids with a larval morphology cannot employ the same processing mechanism as metamorphic animals because of morphological constraints, including the lack of a exible tongue with su cient internal movement-potential and diverging dentition patterns in larval morphotypes [15,16]. To address the question of how processing differs between larval and metamorphosed salamandrid morphotypes of the same species, we examined heterochronic morphotypes of adult Alpine newts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that metamorphosed salamandrid newts use loop-like movements of their hyobranchial apparatus (i.e., tongue) to translate food across the palatal dentition (i.e., tongue-palate rasping) [21]. It has also been suggested that salamandrids with a larval morphology cannot employ the same processing mechanism as metamorphic animals because of morphological constraints, including the lack of a exible tongue with su cient internal movement-potential and diverging dentition patterns in larval morphotypes [15,16]. To address the question of how processing differs between larval and metamorphosed salamandrid morphotypes of the same species, we examined heterochronic morphotypes of adult Alpine newts.…”
Section: Discussionmentioning
confidence: 99%
“…The musculoskeletal components of the feeding apparatus of paedomorphic and post-metamorphic specimens were reconstructed from μCT scans [15]. timescales (x-axes) for comparison.…”
Section: Anatomical Analysis (µCt)mentioning
confidence: 99%
“…Prior studies have hypothesized that, due to their different morphologies, heterochronic morphotypes differ in their feeding performance (capture success-rate) and feeding behavior [12][13][14]. Behavioral studies have shown that paedomorphs tend to have greater aquatic prey capture performance [12,14], but surprisingly, despite diverging prey capture performance and major differences in head morphology, there are only minor differences in prey capture kinematics between heterochronic morphotypes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Second, processing might be affected more from differing feeding apparatus morphologies than capture and transport. This latter point becomes more evident if we consider changes in the structure, position and number of the teeth [26][27][28][29]; structural changes of the hyobranchial apparatus (i.e., developing from a gill-bearing to a tongue-bearing apparatus) [14,15,[30][31][32]; changes in the muscular and ligamentous suspension of the hyobranchial apparatus [33][34][35]; morphological changes of mandible and skull [15,[36][37][38]; as well as dramatic muscular reorganization [39,40] during metamorphosis in salamanders. All of the aforementioned characteristics impact intraoral food processing kinematics in salamanders [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have hypothesized that, due to their different morphologies, heterochronic morphotypes differ in their feeding performance (capture success-rate) and feeding behavior [11][12][13]. Behavioral studies have shown that paedomorphs tend to have greater aquatic prey capture performance [11,13], but surprisingly, despite diverging prey capture performance and major differences in head morphology, there are only minor differences in prey capture kinematics between heterochronic morphotypes [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%